PERSEPSI MASYARAKAT WANASARI AGRABINTA TERHADAP FUNGSI BPD : PERAN KAPASITAS INDIVIDU DAN KOMUNIKASI ORGANISASI - Neli Yuliawati; Rachmat Rachmat; Yeni Sopiatun Nursapitri (PT. ABIG RIZKY PUBLISHER, 2026)
This study aims to analyze the influence of individual capacity and organizational communication on community perceptions of the institutional performance of the Village Consultative Body (BPD) in Wanasari Village, Agrabinta District, Cianjur Regency. The study employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to community members who have interacted with village government services. The analysis was conducted using Structural Equation Modeling based on Partial Least Squares. The results indicate that individual capacity has a positive and significant effect on community perception, with a coefficient value of 0.586. Meanwhile, organizational communication also shows a positive and significant effect, with a coefficient value of 0.388. Simultaneously, both variables explain 0.901 of the variance in community perception, indicating that the research model has a very strong explanatory power. These findings highlight that the quality of human resources and the effectiveness of organizational communication are key determinants in enhancing public trust and evaluation of BPD performance. Therefore, strategic efforts are required to strengthen individual capacity through continuous training and to improve transparent and participatory communication systems in order to support better village governance.